#### Answer

False.
New true statement: 5(x - 4) + 3(x - 4) = 8(x - 4) = 8x - 32

#### Work Step by Step

5 + 3(x - 4) = 8(x - 4) = 8x - 32
Simplifying the Left-hand side:
5 + 3(x - 4)
=5 + 3x-12
=3x-7
Right-Hand Side = 8x - 32
Left-hand side$\ne$Right-Hand Side
Thus the statement is false.
In order to make the statement true, add (x-4) beside 5.
This will make 5 be multiplied by (x-4).
(x-4) are now common factors and can then be grouped together to form 8(x - 4)
New statement:
5(x - 4) + 3(x - 4) = 8(x - 4) = 8x - 32